Pemberdayaan Ibu Hamil dan Kader Kesehatan dalam Penerapan Program Stimulasi Pralahir - Santi Wahyuni; Badriah Badriah; Isnar Nurul Alfiyah (Jurnal Medika: Medika, 2024)
Delays in a child's growth and development can be caused by a lack of stimulation. Some pregnant women do not know, do not realize and have a bad attitude in providing prenatal stimulation. Not all health service facilities provide classes for pregnant women that are equipped with prenatal stimulation programs. Even though parents play an important role in providing stimulation since the fetus is in the womb. Providing prenatal stimulation supports the child's growth and development after birth. Based on this urgency, there is a need for training for pregnant women and health cadres. The aim of this community service is to increase knowledge, awareness and ability of pregnant women in providing prenatal stimulation, as well as increasing community participation in supporting the implementation of prenatal stimulation programs. The results showed an increase in the knowledge aspect of 27.28 points, with an average pre-test score of 64.54 (fair category), post- test 91.82 (good category). The average ability to perform prenatal stimulation was in the good category (94.55). These results show that this training can increase participants' knowledge and abilities in carrying out prenatal stimulation programs.